THE EFFECTIVENESS OF USING EDMODO TO TEACH WRITING ANALYTICAL EXPOSTION TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 GROGOL - Nugraha, Nanda Adhnan Arif; Kurniawan, Erwin Hari (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
Edmodo is a proper Learning Management System (LMS) in teaching writing. Edmodo was chosen because the features of Edmodo can help students to write their ideas. This research was intended to know the effectiveness of using Edmodo to teach writing analytical exposition text. this research used quantitative approach, while the design used was posttest-only control group design. In this research used two classes, there are experimental group and control group. In the experimental group used Edmodo, and in the control group was taught using conventional teaching. To collect the data, post writing test in experimental and control group were administered. Data were analyzed by using mean scores, standard deviation, and independent sample t-test. In result of this research showed that p value was lower than alpha value. It can be concluded that using Edmodo to teach writing analytical exposition is effective.